Home Telehealth Technologies for Heart Failure: An Examination of Adherence Among Veterans - Guzman-Clark, Jenice (J Gerontol Nurs, 2020)
The current retrospective cohort study uses Department of Veterans Affairs (VA) clinical and facility data of Veterans with heart failure enrolled in the VA Home Telehealth (HT) Program. General estimating equations with facility as a covariate were used to model percent average adherence at 1, 3, 6, and 12 months post-enrollment. Most HT patients were White, male, and of older age (mean = 71 years). Average adherence increased the longer patients remained in the HT program. Number of weekly reports of HT use, not having depression, and being of older age were all associated with higher adherence. Compared to White Veterans, Black and other non-White Veterans had lower adherence. These findings identify subgroups of patients (e.g., those with depression, of younger age, non-White) that may benefit from additional efforts to improve adherence to HT technologies.